Effective interventions for reducing diabetes distress: systematic review and meta-analysis. Issue 2 (August 2015) - Sturt, Jackie; Dennick, Kathryn; Hessler, Danielle; Hunter, Benjamin M.; Oliver, Jennifer; Fisher, Lawrence
Abstract : Aims: To identify randomised controlled trials (RCTs) in which diabetes distress (DD) was assessed in adults under experimental conditions and to undertake meta-analysis of intervention components to determine effective interventions for reducing DD. Methods: Systematic review searching Medline, Psychinfo and Embase to March 2013 for studies measuring DD. Two reviewers assessed citations and full papers for eligibility based on RCT design and Problem Areas in Diabetes Scale or Diabetes Distress Scale outcome measure. Interventions were categorised by content and medium of delivery. Meta-analyses were undertaken by intervention category where ≥7 studies were available. Standardised mean differences and 95% confidence intervals were computed and combined in a random effects meta-analysis. Results: Of 16 627 citations reviewed, 41 RCTs involving 6650 participants were included. Twenty-one a priori meta-analyses were undertaken. Effective interventions were psycho-education (−0.21 [−0.33, −0.09]), generalist interventionist (−0.19 [−0.31, −0.08]), ≥6 sessions (−0.14 [−0.26, −0.03]) and ≥3 months duration (−0.14 [−0.24, −0.03]). Motivational interviewing reduced DD (−0.09 [−0.18, −0.00]) and improved baseline elevated glycaemia (−0.16 [−0.28, −0.04]). Although statistical significance was observed most effect sizes were below 0.2. Conclusion: The review signposts interventions likely to reduce elevated DD in Type 1 and Type 2 and across the age profile. Interventional research is needed and warranted targeting elevated distress.